2023
DOI: 10.1371/journal.pwat.0000145
|View full text |Cite
|
Sign up to set email alerts
|

Gridded precipitation products on the Hindu Kush-Himalaya: Performance and accuracy of seven precipitation products

Abstract: Climate change is expected to change precipitation and temperature patterns, which will impact the hydrological regime in Asia. Most river systems in the region originate from the Hindu Kush-Himalayas, and the altered precipitation patterns pose a threat to their sustainability, making it a major concern for planners and stakeholders. Obtaining accurate data on precipitation distribution is crucial for water accounting, which poses challenge. To address this, gridded precipitation products developed from satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Furthermore, APHRODITE performed well in Z1 and Z2, particularly for dry classes, aligning with previous findings (Mishra et al, 2023;Lai et al, 2020;Han & Zhou, 2012;Khandu et al, 2016;Bhardwaj et al, 2017). In contrast, CHIRPS displayed better performance for wet classes, exhibited a general overestimation tendency (Mishra et al, 2023;Aadhar & Mishra, 2017), and showed weaker performance in high-elevation regions (Khandu et al, 2016), as seen in Figure 10.…”
Section: Spi Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, APHRODITE performed well in Z1 and Z2, particularly for dry classes, aligning with previous findings (Mishra et al, 2023;Lai et al, 2020;Han & Zhou, 2012;Khandu et al, 2016;Bhardwaj et al, 2017). In contrast, CHIRPS displayed better performance for wet classes, exhibited a general overestimation tendency (Mishra et al, 2023;Aadhar & Mishra, 2017), and showed weaker performance in high-elevation regions (Khandu et al, 2016), as seen in Figure 10.…”
Section: Spi Analysissupporting
confidence: 89%
“…It is important to note that spatial averaging within each zone and data-filling processes may have impacted the comparison results (Awchi & Suliman, 2021;Trenberth et al, 2014) variations contributed to differences between SbPPs and GS (Zhong et al, 2019;Awchi & Suliman, 2021). Furthermore, APHRODITE performed well in Z1 and Z2, particularly for dry classes, aligning with previous findings (Mishra et al, 2023;Lai et al, 2020;Han & Zhou, 2012;Khandu et al, 2016;Bhardwaj et al, 2017). In contrast, CHIRPS displayed better performance for wet classes, exhibited a general overestimation tendency (Mishra et al, 2023;Aadhar & Mishra, 2017), and showed weaker performance in high-elevation regions (Khandu et al, 2016), as seen in Figure 10.…”
Section: Spi Analysissupporting
confidence: 85%
See 2 more Smart Citations
“…The most promising alternative involves incorporating worldwide data, such as high-resolution daily precipitation datasets like ERA5-Land (European Center for Medium-Range Weather Forecasts fifth generation), satellite precipitation data from CMORPH (Climate Prediction Center Morphing Technique), CPC UPP (Climate Prediction Center Unified Precipitation Project), APHRODITE (Asian Precipitation Highly Resolved Observational Data), and TRMM (Tropical Rainfall Measuring Mission). Satellite and reanalysis precipitation products require evaluation against in-situ data and calibration to hydrological models before use, with varying regional impacts on product performance [22,23].…”
Section: Introductionmentioning
confidence: 99%